Pre-IPO ownership structure and its impact on the IPO process - Alavi, Arash; Pham, Peter Kien; Pham, Toan My (Journal of Banking & Finance, 2008)
We investigate the impact of pre-issue ownership structure on the key decisions surrounding an IPO. We find that managerial ownership is significantly related to (1) the proportion of shares offered, (2) share allocation, and (3) direct issue-related expenses. This suggests that pre-IPO ownership by managers influences their incentive to maintain control and to lower the cost of going public. In comparison, large pre-IPO non-managerial shareholders are more concerned about exiting, and their presence tends to increase issue size and costs. Our findings indicate that differences in pre-IPO owners’ incentives and bargaining power as implied by their pre-IPO shareholdings can significantly influence the IPO process.